PENGEMBANGAN FLIPBOOK PANDA UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS IV SD PADA MATERI PERUBAHAN WUJUD BENDA - Rafika Nur'azizah; Ali Ismail; Regina Lichteria Panjaitan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a learning media product in the form of a PANDA flipbook to improve students' conceptual understanding of the material on changes in the state of matter of grade IV SDN Sukanagara, Sumedang Regency. The research method used is the R&D (Research & Development) method by utilizing the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The research instruments used include interview guidelines, validation sheets for media experts and material experts, student response questionnaires, and test question instruments. The validation results by media experts showed a score of 88.5% which is included in the very feasible category, while the validation results of material experts reached a score of 93.5% with a very feasible category, and for user responses, namely grade IV students obtained an average score of 86% in the range indicating very satisfactory usability. In addition, the results of the pretest and posttest showed a significant increase in students' conceptual understanding after implementing learning using the PANDA flipbook media. Based on the paired sample t-test, the average pretest score was 54.20, increasing to 78.67 in the posttest, and the n-gain test result was 0.5650, which is included in the moderate category. Thus, the development of PANDA flipbook learning media is feasible to be used in learning and is effective in helping students understand the concept of the material better.